Efficacy and safety of CO2 laser in the treatment of chronic wounds: A Retrospective Matched Cohort Trial. Issue 4 (15th November 2021) - Guan, Haonan; Zhang, Di; Ma, Xian; Lu, Yechen; Dong, Jiaoyun; Niu, Yiwen; Liu, Yingkai; Lu, Shuliang; Xu, Jiping; Tang, Jiajun
Abstract: Objectives: Treating chronic cutaneous wounds is challenging, and debridement is a central concept in treating them. Studies have shown that CO2 laser debridement can control local infection and promote the wound healing process. The present study aimed to investigate the efficacy and safety of fully ablative CO2 laser debridement compared to routine surgical debridement in the treatment of chronic wounds. Methods: The retrospective cohort study was conducted on patients with chronic (>1 month) cutaneous wounds (≥1 cm 2 ) between December 1, 2017, and December 1, 2020, in the Wound Healing Center at Shanghai Ruijin Hospital, China. Patients treated with CO2 laser debridement with a DEKA SmartXide2 C80 (DEKA) (the CO2 laser group) were compared with matched control patients with similar baseline characteristics who had undergone routine surgical debridement (the routine group). The primary outcome was time‐to‐heal (days) for chronic wounds in two groups, and secondary outcomes included the wound area and BWAT (Bates–Jensen wound assessment tool) score before treatment, and at 1, 2, 3, and 4 weeks after treatment. Results: The study included 164 patients (82 in the CO2 laser group and 82 matched in the routine group). The time‐to‐heal for patients in the CO2 laser group (41.30 ± 17.11) was significantly shorter than that of the patients in the routine group (48.51 ± 24.32) ( p = 0.015). At 3 and 4 weeks after treatment, the absolute wound area of the CO2 laser group was significantly smaller than that of the routine group. Also, the CO2 laser group exhibited a significantly lower relative area at 2, 3, and 4 weeks after treatment. The CO2 laser group yielded significantly lower BWAT scores at 2, 3, and 4 weeks after treatment. Additionally, the relative BWAT score was significantly lower in the CO2 laser group than the relative scores in the routine group at 2, 3, and 4 weeks after treatment. No adverse events related to the treatments were observed in either group during the study period. Conclusions: The present study has shown that fully ablative CO2 laser debridement has several advantages over routine sharp surgical debridement. It is superior at ameliorating wound status and reducing wound area, and it also significantly reduces the time‐to‐heal for chronic wounds, without causing any adverse events.